Confiscation as one of the methods ro protect intellectual property rights - Olexander, Svitlychnyy (2023)
It is well-known fact that products and goods produced with the usage of the object of intellectual property rights has additional demand, bring additional profits to their right holders, and as a result such goods often become the object of offenses. It has been indicated that, taking into account the unsatisfactory situation of intellectual property protection and the problems of the state system of intellectual property, Ukraine, like the entire civilized world, pays attention to ensuring private and public interests in the field of intellectual property. The authors of the article have analyzed the situation of legal protection and have paid attention to the measures taken by Ukraine to reform the state system of intellectual property. It has been established that social relations in the researched area concern criminal and administrative legal mechanisms related to seizing. It has been emphasized that different types of fines, criminal or administrative confiscation are applied to the violator depending on the violation of the legal norm. The authors have analyzed national and foreign regulatory legal acts, where attention is focused on one of the types of penalty – confiscation. The shortcomings of the Ukrainian legislation have been pointed out and amendments to it have been offered for the purpose of its improvement.